Evaluation of Professional Ethics Indicators of Managers in Small and Medium Enterprises - Roozitalab, Arvin; Rabiee Mandejin, Mohammad Reza; Safarzadeh, Hossein; Momeni, Mandan (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2025)
Objective: The objective of this study is to evaluate the professional ethics indicators of managers in small and medium-sized enterprises (SMEs).Methods and Materials: This research adopted a quantitative approach, with a sample of 380 active managers from SMEs in Tehran. A stratified random sampling method was used to select the sample. The data collection process included both library-based resources and field methods, such as the Delphi technique, to gather expert opinions on the questionnaire items. The data were analyzed using Partial Least Squares (PLS) software for structural equation modeling, due to the non-normality of the data as confirmed by the Kolmogorov-Smirnov test.Findings: The study revealed that organizational justice was the most significant factor influencing professional ethics in SMEs, followed by leadership and management. Organizational culture was identified as an area that required further development, as it scored relatively lower in ethical adherence. The findings also indicated that the majority of managers in the sample were male, aged between 41-50 years, and held postgraduate degrees. The results from the factor loadings, convergent validity, and Fornell-Larcker test confirmed that the measurement model had adequate reliability and validity.Conclusion: This study underscores the importance of professional ethics in enhancing organizational performance in SMEs. It highlights the need for stronger organizational culture and leadership that prioritizes fairness and transparency. Future research should focus on exploring strategies to improve ethical practices in SMEs, especially in regions with diverse business environments like Tehran.